Oral Malignant Acanthosis Nigricans: An Early Diagnostic Sign for Ovarian Carcinoma: A Case Report - Liu Y; Wu X; Chen S; Meng W (Dove Medical Press, 2024)
Yang Liu,* Xiaoli Wu,* Siting Chen, Wenxia Meng Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, 510280, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenxia Meng, Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, 510280, People's Republic of China, Email mengwx2008@foxmail.comAbstract: Acanthosis nigricans (AN) is a dermatological condition characterised by the symmetrical development of velvety, hyperpigmented plaques predominantly in intertriginous areas such as the axillae, neck, inframammary regions, and groin. The malignant variant of AN is frequently associated with internal malignancies, particularly gastric adenocarcinoma, accounting for 55- 61% of cases. Patients exhibiting characteristic skin lesions are commonly initially evaluated in dermatology departments. This case report details a rare instance of a patient diagnosed with malignant acanthosis nigricans, presenting with only a mild form of florid oral papillomatosis concomitant with ovarian carcinoma. The early identification and management of these subtle clinical manifestations enabled timely intervention for the tumor, resulting in patient survival. There are few reported cases of malignant acanthosis nigricans associated with ovarian cancer. Oral medicine specialists should be cognisant of conditions manifesting as extensive oral papillary hyperplasia, and the possibility of an underlying malignant disease should be considered, particularly in cases of elderly-onset AN presenting exclusively with oral lesions.Keywords: malignant acanthosis nigricans, ovarian cancer, papillary hyperplasia